Formulasi Granul Sereal Daun Kelor dengan Variasi Jenis Pengikat dan Konsentrasi Xanthan Gum - Karina Citra Rani; Nani Parfati; Endang Wahyu Fitriani; Dina Novita Sari; Hilmiyatul Islamia; Tiara Yuni Wulansari (Fakultas Farmasi Universitas Pancasila, 2021)
Moringa leaves contain macronutrients and micronutrients, potential to be developed into cereal products in the form of granules using the wet granulation method. The type of binder and the concentration of the suspending agent are the main factors that affect the physical characteristics and proximate content of cereals. In this research, 6 formulas of cereal granules were optimized with various types of binders (arrowroot flour, sorghum flour, cornstarch) and variations in the concentration of xanthan gum (0.5% and 1.0%). This study aims to obtain a granule formula of Moringa leaf cereal that meets the requirements of physical, chemical, proximate, and heavy metal characteristics. The results of the evaluation of the granule characteristics showed that all Moringa leaf cereal formulas had good flow characteristics. The results of the evaluation of cereal characteristics after reconstitution showed that cereal granules dispersed quickly (12.58–16.45 seconds), viscosity 73.75 -245 cps, pseudoplastic flow characteristics, and met the pH requirements of food products (5.00-6.00). The results of proximate analysis and metal content showed that all cereal formulas met the SNI requirements for cereal milk (SNI 01-4270-1996) in terms of protein, carbohydrate, ash, lead (Pb), and copper (Cu) content parameters. The most optimal cereal formula is formula 2 because it shows physical characteristics, fat content, carbohydrates, protein, and heavy metals that meet the requirements, as well as crude fiber content (0.76%) which is closest to the requirements (0.7%).